TAFAKKUR SEBAGAI KONSEPSI MENUJU KEABADIAN MANUSIA MODERN: (Telaah Tafsir Surah Ali-Imran Ayat 190-191) - Hasanah, Uswatun; Hartono, Hartono (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
The purpose of this study is to understand human identity as a servant in an era where technological sophistication is rapidly increasing which causes humans to be preoccupied with the virtual world. The millennial generation who spends their time chatting, Facebook, Whatsapp, Instagram, YouTube and so on, forgets about their future. This research uses the library research method (library), with a descriptive-analytical method through the religious theology approach. As stated in Surah Ali Imran verses 190-191, in this surah there is also an explanation of ethics for people who meditate, namely by confronting Allah by purifying Him from the futility of creating something. The results obtained in this study can determine the concept of tafakkur, namely faith, ulul albab, dhikr, meditating which then ends with prayer. In this study, we also know the correlation of contemplation to the prevention of environmental damage to devotion in the goodness of the world to the hereafter. If a person or group from the community always applies the content contained in Surah Ali Imran verses 190-191, it can reduce activities that are not useful, useless and will automatically increase the quality of one's faith. This faith will give birth to humans who have good morals and mentality, so that they can overcome environmental damage and eternal goodness throughout time.